PERANAN PASRAMAN PENYANG HINJE SIMPEI DALAM EDUKASI PENCEGAHAN STUNTING BAGI UMAT HINDU DI KOTA KASONGAN, KABUPATEN KATINGAN, PROVINSI KALIMANTAN TENGAH - Megawati, Megawati; Pranata, Pranata; Subagiasta, I Ketut; Gunawan, I Gede Dharman; Riandi, Riandi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
Pasraman Penyang Hinje Simpei Kasongan as a Hindu educational institution has an important role in maintaining and disseminating Hindu religious, cultural, and spiritual values ​​to the younger generation. The formation of children's characteristics with good education will create good children or suputra children, education is needed in learning. However, the presence of stunting is a marker of the risk of poor child development for pasraman children. Therefore, stunting prevention education is needed that aims to ensure that Pasraman Penyang Hinje Simpei children can grow and develop optimally and maximally, accompanied by emotional, social, and physical abilities that are ready to learn. This study aims to find and obtain facts, data and descriptions of strategies and efforts made in stunting prevention education through Hindu educational institutions in Kasongan City, Katingan Regency. The method used in this study uses a research method with a qualitative approach. The results of the study found strategies for stunting prevention through Hindu educational institutions as well as stunting prevention education efforts through Hindu educational institutions in Kasongan City, Katingan Regency.